An Analysis of Educational Policies Related to The Implementation of The Merdeka Curriculum in Madrasah - Putri, Rahmi; Gunawan, Rilla Gina; Ramadhani, Yulia Rizki; Gistituati, Nurhizrah; Rusdinal, Rusdinal (Universitas Veteran Bangun Nusantara, 2023)
The implementation of the Merdeka Curriculum in madrasahs, guided by the Ministry of Religious Affairs Regulation (KMA) Number 347 in 2022, offers both advantages and challenges. This policy empowers madrasahs in Indonesia to develop education unit-level curricula that cater to the specific needs and management of education. The advantages of implementing the Merdeka Curriculum lie in its ability to respect and enhance Islamic education. Madrasahs can emphasize religious understanding, Quranic studies, and character education, enabling students to deepen their religious knowledge and strengthen their religious identities. Moreover, the curriculum's flexibility allows madrasahs to tailor educational experiences to the needs, social contexts, and local cultures of their students, making learning more relevant and meaningful. By incorporating practical and contextual subjects, the Merdeka Curriculum facilitates the development of broader skills, equipping students with academic, social, and life skills essential for their holistic growth. However, challenges arise in implementing the Merdeka Curriculum. Educators need comprehensive training and professional development to effectively design and implement a flexible curriculum. Ensuring consistent education standards across madrasahs is also crucial, as the freedom to determine curricula may result in variations. Integration with the national curriculum is essential to ensure that fundamental subjects such as literacy, numeracy, and general knowledge are adequately covered.